2019
DOI: 10.5194/acp-19-7927-2019
|View full text |Cite
|
Sign up to set email alerts
|

Can downwelling far-infrared radiances over Antarctica be estimated from mid-infrared information?

Abstract: Abstract. Far-infrared (FIR: 100cm-1<wavenumber, ν<667 cm−1) radiation emitted by the Earth and its atmosphere plays a key role in the Earth's energy budget. However, because of a lack of spectrally resolved measurements, radiation schemes in climate models suffer from a lack of constraint across this spectral range. Exploiting a method developed to estimate upwelling far-infrared radiation from mid-infrared (MIR: 667cm-1<ν<1400 cm−1) observations, we explore the possibility of inferring zenith FIR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, many following studies have shown the importance of FIR and its strength in remote sensing the atmospheric properties in the upper troposphere (e.g., Harries et al., 2008). For example, several studies showed that a large fraction of the OLR energy lies in the FIR region (Bellisario et al., 2019; Chen et al., 2014; Harries et al., 2008; X. Huang et al., 2008; Martinazzo et al., 2021; Turner & Mlawer, 2010). Moreover, as the OLR in FIR is especially sensitive to atmospheric water vapor and clouds (e.g., cirrus), investigations and observations in FIR could potentially improve the retrieval of their information (Blanchet et al., 2011; Clough et al., 1992; Cox et al., 2015; Delamere et al., 2010; Harries et al., 2008; Libois & Blanchet, 2017; Maestri & Rizzi, 2003; Magurno et al., 2020; Palchetti et al., 2015, 2016; Sinha & Harries, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, many following studies have shown the importance of FIR and its strength in remote sensing the atmospheric properties in the upper troposphere (e.g., Harries et al., 2008). For example, several studies showed that a large fraction of the OLR energy lies in the FIR region (Bellisario et al., 2019; Chen et al., 2014; Harries et al., 2008; X. Huang et al., 2008; Martinazzo et al., 2021; Turner & Mlawer, 2010). Moreover, as the OLR in FIR is especially sensitive to atmospheric water vapor and clouds (e.g., cirrus), investigations and observations in FIR could potentially improve the retrieval of their information (Blanchet et al., 2011; Clough et al., 1992; Cox et al., 2015; Delamere et al., 2010; Harries et al., 2008; Libois & Blanchet, 2017; Maestri & Rizzi, 2003; Magurno et al., 2020; Palchetti et al., 2015, 2016; Sinha & Harries, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…FIR spectral measurements of DLR proved valuable for refining the knowledge of water vapour spectroscopy (Mlawer et al, 2019) and testing the ability to model radiative transfer in the atmosphere (Mlynczak et al, 2016;Mast et al, 2017;Bellisario et al, 2019;Mlawer et al, 2019). In addition, ground-based FIR observations were successfully exploited to infer cloud properties (Maestri et al, 2014;Rizzi et al, 2016;Di Natale et al, 2017), to retrieve the thermal structure and composition of the atmosphere (Rizzi et al, 2018;Bianchini et al, 2019), and to conduct radiative closure studies (Delamere et al, 2010;Sussmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, measurements of the downwelling longwave radiation, including in the FIR, have been used to study the cirrus cloud radiative properties, both at mid-latitudes (Palchetti et al, 2016;Di Natale et al, 2021;Maestri et al, 2014) and in polar regions, in particular in Arctic (Garrett and Zhao, 2013;Intrieri et al, 2002;Ritter et al, 2005) and Antarctica (Maesh et al, 2001a, b;Palchetti et al, 2015;Di Natale et al, 2017;Rowe et al, 2019;Rathke et al, 2002;Maestri et al, 2019;Bellisario et al, 2019).…”
Section: Introductionmentioning
confidence: 99%